EFEKTIVITAS PELICAN CROSSING SEBAGAI MEDIA PENYEBERANGAN - Fauba, Andrean; Prayogi, Galih Rio; Andry , Yuliyanto; Michael; Gutama, Detha Sekar Langit Wahyu; Ruslin (RENOVASI : Rekayasa Dan Inovasi Teknik Sipil, 2025)
Based on direct observations at the pelican crossing located on Jalan Raden Intan, Bandar Lampung, despite the presence of pedestrian crossing facilities, many vehicle users do not stop or give way to pedestrians. Additionally, there are issues with pedestrian behavior, including disorderly crossing. Therefore, it is necessary to analyze the effectiveness of the pelican crossing on Jalan Raden Intan, Bandar Lampung, based on public perceptions, pedestrian crossing volume, the impact of traffic on pedestrians, the adequacy of crossing facilities, and to propose improvements for the pelican crossing. The analysis was conducted using questionnaires with indicators of safety, comfort, security, convenience, and accessibility. Effectiveness analysis was performed using PV2 calculations and traffic impact analysis on pedestrians. The results from the questionnaires indicated that the pelican crossing is very ineffective in terms of safety, comfort, security, convenience, and accessibility. The PV2 value of 1.46 x 109 suggests that Jalan Raden Intan, Bandar Lampung, requires a pelican crossing with a waiting area. The effectiveness analysis yielded scores of 54.66% and 50.44%, indicating that the pelican crossing at the observed location is categorized as ineffective. The traffic impact analysis showed that vehicle speeds before, during, and after the crossing do not decrease significantly, only reducing the speed of vehicles in the presence of pedestrians. Recommendations from this study include planning pedestrian crossings for individuals with special needs.